Faktor-Faktor Yang Mempengaruhi Kelulusan Tepat Waktu Alumni Mahasiswa D3 Komputerisasi Akuntansi Universitas STEKOM (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to examine and analyze the direct and simultaneous effects of financial stress, financial management, financial parenting, and enrollment interruption on the timely graduation of alumni from the D3 Computerized Accounting program at STEKOM University. Using a quantitative approach, the study involved 84 alumni as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics software. The findings reveal that financial stress does not have a significant direct effect on timely graduation. In contrast, financial management, financial parenting, and enrollment interruption each have a significant direct effect on timely graduation. Furthermore, when analyzed simultaneously, financial stress, financial management, financial parenting, and enrollment interruption collectively have a significant effect on the timely graduation of alumni. These results highlight the importance of good financial management practices, parental financial guidance, and uninterrupted study patterns in supporting students to graduate on time. The study contributes to understanding the financial and academic factors influencing graduation timelines and provides practical insights for educators, parents, and policymakers in improving student success rates.